2019
DOI: 10.1016/j.cortex.2018.01.017
|View full text |Cite
|
Sign up to set email alerts
|

The problem of detecting long-term forgetting: Evidence from the Crimes Test and the Four Doors Test

Abstract: While most individuals who have problems acquiring new information forget at a normal rate, there have been reports of patients who show much more rapid forgetting, particularly comprising a subsample of patients with temporal lobe epilepsy. Currently available tests are generally not designed to test this since it requires multiple different tests of the same material. We describe two tests that aim to fill this gap, one verbal, the Crimes Test, the other visual, the Four Doors Test. Each test involves four s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
73
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(81 citation statements)
references
References 30 publications
2
73
6
Order By: Relevance
“…The authors suggested that the testing of individual features (subsamples of questions) enabled participants to remember the entire episode which then acted as a further reminder. This lack of forgetting in healthy individuals could provide an ideal test of ALF by avoiding the danger of floor effects (Baddeley et al, 2019). In the current study, we have addressed the question of whether or not ALF does characterise the memory deficits of AD patients using the procedures devised by Baddeley et al (2019) and designed material closely following The Crimes Test (Baddeley et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors suggested that the testing of individual features (subsamples of questions) enabled participants to remember the entire episode which then acted as a further reminder. This lack of forgetting in healthy individuals could provide an ideal test of ALF by avoiding the danger of floor effects (Baddeley et al, 2019). In the current study, we have addressed the question of whether or not ALF does characterise the memory deficits of AD patients using the procedures devised by Baddeley et al (2019) and designed material closely following The Crimes Test (Baddeley et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In an attempt to address the difficulties arising with repeated testing, a number of approaches have been identified (for a review see Elliot et al, 2014). Baddeley et al (2019) propose to use material that once learned can be used to test the same individual over longer delays, repeatedly, without testing the same information on each occasion. From the review of the 14 studies on ALF in AD, listed in Table 1, the issue of whether or not the same material was retested on each delay emerges as one of the differentiating factors between studies that have reported ALF and those which have not.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…while the paradigm employed during evaluation (recall, cued recall, and recognition) probably allows detection of distinct memory processes [10]. There are methodological recommendations to prevent bias during ALF testing and improve the patient experience [10,103]. These include testing for both verbal and visuospatial items, evaluating both recall and recognition, avoiding short-term memory influence (by prolonging the first testing interval) and ceiling, floor, and rehearsal effects.…”
Section: Detecting Alf In Clinical Practicementioning
confidence: 99%
“…These include testing for both verbal and visuospatial items, evaluating both recall and recognition, avoiding short-term memory influence (by prolonging the first testing interval) and ceiling, floor, and rehearsal effects. Further, new tests of both verbal and visuospatial memory are being explored for their potential use in ALF experiments [103]. Incidental memory tests may also be a practical solution as they would detect ALF for real-life events and be easy to effectuate in the clinical setting [45].…”
Section: Detecting Alf In Clinical Practicementioning
confidence: 99%